2021
DOI: 10.2147/cmar.s322179
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of m6A-Related lncRNAs for Prognosis Value and Response to Immune Checkpoint Inhibitors Therapy in Hepatocellular Carcinoma

Abstract: Introduction: N6-methyladenosine (m6A) modification and long non-coding RNAs (lncRNAs) play pivotal roles in the progression of hepatocellular carcinoma (HCC). However, how their interaction is involved in the prognostic value of HCC and immune checkpoint inhibitors (ICIs) therapy remains unclear. Methods: The RNA sequencing and clinical data of HCC patients were collected from TCGA database. The prognostic m6A-related lncRNAs were screened out with Pearson correlation test, univariate Cox analysis and least a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Consensus clustering analysis was performed to obtain two clusters. The role of N6-methyladenosine (m6A)-associated lncRNAs in immune infiltration and prognosis of HCC have been previously illustrated by Wang et al ( Wang et al, 2021a ), who similarly divided the TCGA liver cancer cohort into Clusters 1 ( n = 313) and 2 ( n = 57) based on consensus clustering analysis; Cluster 1 had a superior prognosis compared to Cluster 2 ( p < 0.001). This is consistent with our analysis, where Cluster 1 had a better prognosis than Cluster 2 in our cohort ( p < 0.001) ( Figure 4B ).…”
Section: Discussionmentioning
confidence: 96%
“…Consensus clustering analysis was performed to obtain two clusters. The role of N6-methyladenosine (m6A)-associated lncRNAs in immune infiltration and prognosis of HCC have been previously illustrated by Wang et al ( Wang et al, 2021a ), who similarly divided the TCGA liver cancer cohort into Clusters 1 ( n = 313) and 2 ( n = 57) based on consensus clustering analysis; Cluster 1 had a superior prognosis compared to Cluster 2 ( p < 0.001). This is consistent with our analysis, where Cluster 1 had a better prognosis than Cluster 2 in our cohort ( p < 0.001) ( Figure 4B ).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the predictive accuracy of the risk score was assessed by the time-dependent ROC analysis at 1, 2, and 3 years, with area under the curve (AUC) values of 0.787, 0.761, and 0.739, respectively ( Figure 2H ), Furthermore, the AUC value of OS for the risk score was significantly higher than those for age, sex, tumor stage, tumor pathological grade, and tumor staging ( Figure 2I , Supplementary Figure S3 ). DCA curve and IDI were used to compare the discriminative ability between our model and the previously reported lncRNA prediction model for HCC ( Li et al, 2020 ; Guo et al, 2021a ; Guo et al, 2021b ; Huang et al, 2021b ; Wang et al, 2021b ; Lei et al, 2021 ; Li et al, 2021 ). DCA indicated that our pyroptosis-related lncRNA signature had positive net benefits and superiority compared with the previously reported lncRNA prediction signature for HCC ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al found that glioma patients with high risk had higher expression of immune checkpoint genes, including PDCD1LG2, TNFRSF14, and PDCD1 ( 46 ). Wang et al found increased expression of CD274, CTLA4, HAVCR2, and TIGIT in a high-risk group of HCC patients ( 47 ). Consistent with previous studies, PRlncSig score was positively correlated with the expression levels of immune checkpoint genes (HAVCR2, PDCD1, CD274, CTLA4, and TNFRSF14).…”
Section: Discussionmentioning
confidence: 99%